2018
DOI: 10.1186/s40560-017-0270-8
|View full text |Cite
|
Sign up to set email alerts
|

The Japanese Clinical Practice Guidelines for Management of Sepsis and Septic Shock 2016 (J-SSCG 2016)

Abstract: Background and purposeThe Japanese Clinical Practice Guidelines for Management of Sepsis and Septic Shock 2016 (J-SSCG 2016), a Japanese-specific set of clinical practice guidelines for sepsis and septic shock created jointly by the Japanese Society of Intensive Care Medicine and the Japanese Association for Acute Medicine, was first released in February 2017 and published in the Journal of JSICM, [2017; Volume 24 (supplement 2)] 10.3918/jsicm.24S0001 and Journal of Japanese Association for Acute Medicine [201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
83
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 77 publications
(83 citation statements)
references
References 485 publications
(531 reference statements)
0
83
0
Order By: Relevance
“…Several large observational studies have consistently demonstrated favorable effects of antithrombin supplementation in septic patients with DIC . Accordingly, the Japanese Clinical Practice Guidelines for Management of Sepsis and Septic Shock recommends the use of antithrombin to DIC patients with decreased antithrombin activity, although this practice is not common outside of Japan.…”
Section: Treatment For Dic and Sicmentioning
confidence: 99%
“…Several large observational studies have consistently demonstrated favorable effects of antithrombin supplementation in septic patients with DIC . Accordingly, the Japanese Clinical Practice Guidelines for Management of Sepsis and Septic Shock recommends the use of antithrombin to DIC patients with decreased antithrombin activity, although this practice is not common outside of Japan.…”
Section: Treatment For Dic and Sicmentioning
confidence: 99%
“…However, the Japanese Clinical Practice The above controversies on the use of antithrombin may be explained by the KyberSept trial [5]. Umemura [7] and the J-SSCG2016 [30] used the results of subgroup analysis of the KyberSept study conducted on septic DIC patients by Kienast et al [21]. In contrast, Allingstrup [6] used the results of the whole cohort in the KyberSept study [5], which suggested the increase of risk of bleeding complication without any significant effect on mortality for the use of antithrombin.…”
Section: The Use Of Heparin For Septic Dicmentioning
confidence: 99%
“…The use of thrombomodulin for Septic DIC In SSCG 2016 [4], there was no recommendation for the use of thrombomodulin in septic patients. In J-SSCG2016, there is no clear recommendation for the use of thrombomodulin in sepsis-associated DIC (Level B, expert consensus) [30]. The ISTH had recommended to use thrombomodulin in DIC patients (potentially recommended) [29].…”
Section: The Use Of Heparin For Septic Dicmentioning
confidence: 99%
See 2 more Smart Citations